Transcatheter occlusion of a left ventricular outflow tract pseudoaneurysm using a "plug and coil" strategy. Issue 11 (18th September 2022) - Forcillo, Jessica; Robert‐Halabi, Maxime; Soulez, Gilles; Potvin, Jeannot
Abstract: Left ventricular outflow tract pseudoaneurysm is a rare and potentially fatal complication of aortic valve replacement. Surgical repair is the most common treatment and is particularly suitable for large pseudoaneurysms. Recently, there has been significant breakthroughs in the management of postoperative pseudoaneurysms via endovascular techniques. We report a case of a large postoperative pseudoaneurysm of the left ventricular outflow tract that occurred 1 year following a redo mechanical aortic valve replacement in a patient with previous valve sparing procedure performed 5 years earlier. The pseudoaneurysm was anatomically located antero‐laterally between the right atrium and the ascending aorta. Successful occlusion was achieved with an Amplatzer Vascular Plug 2 (Abbott) and several coils (Terumo) via a transapical approach.